Aging Reduces Insulin Clearance in Mice - Marmentini, Carine; Soares, Gabriela M.; Bronczek, Gabriela A.; Piovan, Silvano; Mareze-Costa, Cecília E.; Carneiro, Everardo M.; Boschero, Antonio C.; Kurauti, Mirian A. (Frontiers in Endocrinology, 2021)
Hyperinsulinemia is frequently associated with aging and may cause insulin resistance in elderly. Since insulin secretion and clearance decline with age, hyperinsulinemia seems to be maintained, primarily, due to a decrease in the insulin clearance. To investigate these aging effects, 3- and 18-month-old male C57BL/6 mice were subjected to intraperitoneal glucose and insulin tolerance tests (ipGTT and ipITT) and, during the ipGTT, plasma c-peptide and insulin were measure to evaluate in vivo insulin clearance. Glucose-stimulated insulin secretion in isolated pancreatic islets was also assessed, and liver samples were collected for molecular analyses (western blot). Although insulin sensitivity was not altered in the old mice, glucose tolerance, paradoxically, seems to be increased, accompanied by higher plasma insulin, during ipGTT. While insulin secretion did not increase, insulin clearance was reduced in the old mice, as suggested by the lower c-peptide:insulin ratio, observed during ipGTT. Carcinoembryonic antigen-related cell adhesion molecule-1 (CEACAM1) and insulin-degrading enzyme (IDE), as well as the activity of this enzyme, were reduced in the liver of old mice, justifying the decreased insulin clearance observed in these mice. Therefore, loss of hepatic CEACAM1 and IDE function may be directly related to the decline in insulin clearance during aging.